2019
DOI: 10.12717/dr.2019.23.1.043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endoplasmic Reticulum Stress Inhibitor Treatment during the Micromanipulation of Somatic Cell Nuclear Transfer in Porcine Oocytes

Abstract: We examined the effects of endoplasmic reticulum (ER) stress inhibitor treatment during the micromanipulation of porcine somatic cell nuclear transfer (SCNT) on the in vitro development of SCNT embryos. ER stress inhibitors such as salubrinal (200 nM) and tauroursodeoxycholic acid (TUDCA; 100 μM) were added to the micromanipulation medium and holding medium. The expression of X-box binding protein 1 ( Xbp1 ), ER-stress-associated genes, and apoptotic genes in SCNT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Several studies have shown that ER stress is inhibited when TUDCA is treated to embryo or cell in culture period (Zhang et al, 2012a,b;Yoon et al, 2014;Lin et al, 2015, Mochizuki et al, 2018. In addition, our previous study showed that when TUDCA is treated during the micromanipulation and activation processes of the SCNT embryo, Xbp1s and ER stress-associated genes are significantly reduced, thereby increasing the development and quality of SCNT embryos (Park et al, 2019). This study substantiates our previous result.…”
Section: A B C Dsupporting
confidence: 90%
See 3 more Smart Citations
“…Several studies have shown that ER stress is inhibited when TUDCA is treated to embryo or cell in culture period (Zhang et al, 2012a,b;Yoon et al, 2014;Lin et al, 2015, Mochizuki et al, 2018. In addition, our previous study showed that when TUDCA is treated during the micromanipulation and activation processes of the SCNT embryo, Xbp1s and ER stress-associated genes are significantly reduced, thereby increasing the development and quality of SCNT embryos (Park et al, 2019). This study substantiates our previous result.…”
Section: A B C Dsupporting
confidence: 90%
“…There was no significant decrease in the splicing of Xbp1 in combination with ER stress inhibitor and antioxidant. Previous study showed that the combination of ER stress inhibitor TUDCA and salubrinal did not significantly decrease the Xbp1s and ER stress-associated gene transcription levels, suggesting that simultaneous treatment of both agents would have had an excessive effect on ER (Park et al, 2019). From this point of view, a similar tendency would have been observed when the ER stress inhibitor and antioxidant were simultaneously treated.…”
Section: A B C Dmentioning
confidence: 83%
See 2 more Smart Citations
“…In the conditions where Tudca was added, macrophages had also been pre-incubated with 100 µM Tudca, prior to adding HepG2 cells. This concentration has previously been shown to effectively inhibit ER stress in different cell types [ 55 , 56 ]…”
Section: Methodsmentioning
confidence: 99%